2021
DOI: 10.2147/ijn.s296513
|View full text |Cite
|
Sign up to set email alerts
|

Combined Photothermal and Ionizing Radiation Sensitization of Triple-Negative Breast Cancer Using Triangular Silver Nanoparticles

Abstract: Background Ionizing radiation (IR) is commonly used in triple-negative breast cancer (TNBC) treatment regimens. However, off-target toxicity affecting normal tissue and grueling treatment regimens remain major limitations. Hyperthermia is one of the greatest IR sensitizers, but only if heat is administered simultaneously or immediately prior to ionizing radiation. Difficulty in co-localizing ionizing radiation (IR) in rapid succession with hyperthermia, and confining treatment to the tumor have hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 54 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…There were no nonmalignant mammary epithelial cells saved as a result of this combination. It was shown that thermal radiation sensitization using triangular silver NPs resulted in excellent results despite the lower treatment dose and frequency (Sears et al., 2021 ), excellent results despite the lower treatment dose and frequency (Sears et al., 2021 ). When combined with the histone deacetylase inhibitor SAHA, gold NPs and radio sensitization were tested in 2D and 3D cancer cell cultures.…”
Section: Mechanism Of Cancer-targetingmentioning
confidence: 99%
“…There were no nonmalignant mammary epithelial cells saved as a result of this combination. It was shown that thermal radiation sensitization using triangular silver NPs resulted in excellent results despite the lower treatment dose and frequency (Sears et al., 2021 ), excellent results despite the lower treatment dose and frequency (Sears et al., 2021 ). When combined with the histone deacetylase inhibitor SAHA, gold NPs and radio sensitization were tested in 2D and 3D cancer cell cultures.…”
Section: Mechanism Of Cancer-targetingmentioning
confidence: 99%
“…Although effective for shrinking tumors, LITT is non-curative due to difficulties in achieving clean margins, treatment of large tumors and minimizing damage to a normal brain while treating invasive GBM cells. Depending upon their size and shape, AgNPs can be designed with plasmon resonance frequencies in the NIR spectrum, enabling them to generate heat when excited by wavelengths of light emitted by lasers currently used in interstitial thermal therapy of GBM (e.g., 808 nm and 1064 nm) [ 113 , 114 , 115 ]. One challenge to using AgNPs for photothermal therapy is that they are rapidly etched in biological environments, altering their shape and decreasing their efficiency at converting light to heat.…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…Furthermore, heat itself is a radiosensitizer when given concurrently or immediately prior to ionizing radiation exposure [ 118 ]. Although not yet tested for use in GBM, preclinical studies using AgNPs for combined photothermal treatment and radiation sensitization of breast cancer indicate that the combined sensitizing effects of AgNPs, heat and radiation can selectively kill cancer cells without killing normal cells [ 115 ]. Furthermore, intratumoral injection of AgNPs (10 ug/cm 3 based upon tumor volume) significantly sensitized intracranial C6 glioma tumors in rats to hyperthermia generated by the excitation of superparamagnetic iron oxide nanoparticles (3 mg/cm 3 ) (see Section 2.3 below), indicating that AgNPs may also sensitize GBM to heat-based treatments [ 119 ].…”
Section: Metal-based Nanoparticlesmentioning
confidence: 99%
“…Recently, noble metal nanoparticles, such as Au-based nanocomposites, have been extensively explored for the synergistic therapeutics of PTT and RT due to their strong NIR optical absorption [96][97][98][99][100][101][102]. For instance, Sun et al wrapped gold nanorods with tumor cell membranes to form novel nanocomposites (GNR@Mem).…”
Section: Nanomaterials For Combined Ptt and Rtmentioning
confidence: 99%